Prevalence of pulmonary tuberculosis in homeless individuals in the Addis Ababa City, Ethiopia - Shamebo, Tsegaye; Mekesha, Sindew; Getahun, Muluwork; Gumi, Balako; Petros, Beyene; Ameni, Gobena (Frontiers in Public Health, 2023)
Homeless individuals are at a high risk of infection with Mycobacterium tuberculosis (M. tuberculosis) as compared to the general population. The number of homeless individuals has been increasing in Addis Ababa City during the last three decades due to the migration of rural inhabitants to the City for better living conditions. The objective of this study was to estimate the prevalence of pulmonary tuberculosis (PTB) and evaluate associated risk factors in homeless individuals in Addis Ababa City. A total of 5,600 homeless individuals were screened for PTB symptoms using WHO guideline between February 2019 and December 2020. Sputum samples were cultured from individuals with symptoms of PTB for mycobacterial isolation. Logistic regression analysis was used to identify factors associated with PTB. The prevalence of bacteriologically confirmed cases was 1.1% (59/5,600) or 10.54 per 1000 population. Multinomial logistic regression analysis showed that being homeless for more than five years, body mass index (BMI) less than 18.5, smoking cigarette, living in a group of more than five individuals, close contact with chronic coughers, imprisonment and HIV infection were significantly associated with the prevalence of PTB in homeless individuals (P < 0.05). In conclusion, the result of this study indicated that the prevalence of PTB in homeless individuals was higher than the prevalence of PTB in the general population of Addis Ababa City requiring for the inclusion of the homeless individuals in the TB control program.